Before-Visit Questionnaire: A Tool to Augment Communication and Decrease Provider Documentation Burden in Pediatric Diabetes - Kumah-Crystal, Yaa A.; Stein, Preston M.; Chen, Qingxia; Lehmann, Christoph U.; Novak, Laurie L.; Roth, Sydney; Rosenbloom, S. Trent (Applied Clinical Informatics, 2021)
Objective To develop and evaluate an electronic tool that collects interval history and incorporates it into a provider summary note.Methods A parent-facing online before-visit questionnaire (BVQ) collected information from parents and caregivers of pediatric diabetes patients prior to a clinic encounter. This information was related to interval history and perceived self-management barriers. The BVQ generated a summary note that providers could paste in their own documentation. Parents also completed postvisit experience questionnaires. We assessed the BVQs perceived usefulness to parents and providers and compared provider documentation content and length pre- and post-BVQ rollout. We interviewed providers regarding their experiences with the system-generated note.Results Seventy-three parents of diabetic children were recruited and completed the BVQ. A total of 79% of parents stated that the BVQ helped with visit preparation and 80% said it improved perceived quality of visits. All 16 participating providers reviewed BVQs prior to patient encounters and 100% considered the summary beneficial. Most providers (81%) desired summaries less than 1 week old. A total of 69% of providers preferred the prose version of the summary; however, 75% also viewed the bulleted version as preferable for provider review. Analysis of provider notes revealed that BVQs increased provider documentation of patients' adherence and barriers. We observed a 50% reduction in typing by providers to document interval histories. Providers not using summaries typed an average of 137 words (standard deviation [SD]: 74) to document interval history compared with 68 words [SD 47] typed with BVQ use.Discussion Providers and parents of children with diabetes appreciated the use of previsit, parent-completed BVQs that automatically produced provider documentation. Despite the BVQ redistributing work from providers to parents, its use was acceptable to both groups.Conclusion Parent-completed questionnaires on the patient's behalf that generate provider documentation encourage communication between parents and providers regarding disease management and reduce provider workload.
Keywords: questionnaires; patient engagement; documentation; workflow; outcomes